SUKSESI VEGETASI GUNUNG MERAPI MEGGUNAKAN INDEK NDVI - Betti Yuniasih (AGROISTA : Jurnal Agroteknologi, 2017)
Succession is the natural ecological process to restore the condition after the disturbance happen. The succession caused by pyroclastic flow of the volcano eruption is the example of natural succession. The NDVI Index is the one tools to observe the sucession after burning using the satellite imagery. Aims of this research were to compare the vegetation density in location that was affected by pyroclastic flow and location that was not affected by pyroclastic flow in southern mountainside of Merapi volcano using NDVI index in ASTER imagery that was recorded on July 7, 2009, November 15, 2010, and June 13, 2012. The results showed that before the eruption in 2010, the vegetation density in both of location is almost same. Than the NDVI index in ASTER imagery that was recorded in November 15, 2010 showed the decline of vegetation density in both locations, especially in location that was affected by pyroclastic flow. The location that was affected by pyroclastic flow have the almost same NDVI index with location that was not affected by pyroclastic flow in two years after the eruption, which means there has been a succession.